THE FACTORS ASSOCIATED WITH UNSAFE ACTIONS ON WORKERS PRESS PART MANUFACTURING COMPANY IN TANGERANG INDONESIA - Mahiyaqothrun Nadia; Mugi Wahidin; Mayumi Nitami; Decy Situngkir (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
Background: Work accidents are still a problem in industry both in the world and in Indonesia. The cause of work accidents is 88% due to unsafe acts. This study aimed to determine the factors associated with unsafe acts in workers at the Press Part Manufacturing Company in Tangerang. Methods: The design used was a crosssectional study with a sample size of 69 who were selected using the proportional stratified random sampling method. The dependent variable is unsafe acts while the independent variables include knowledge, attitudes, years of service, OSH supervision and training. Data collection uses primary data by filling out questionnaires filled out by respondents. Univariate and bivariate data analysis with Chi Square test. Results: Univariate and bivariate data analysis with Chi Square test. The results showed that 62.3% of workers who committed unsafe acts had high knowledge of 72.5%, had a negative attitude of 53.6%, had a new working period of 65.2%, had poor supervision of 59. .4%, and 63.8% had attended K3 training. The results of the bivariate analysis showed that there was a relationship between attitude (p-value = 0.007), length of service (p-value = 0.001), and supervision (p-value = 0.046) with unsafe acts.Conclusion: There is a relationship between attitudes, length of service and supervision with unsafe actions